Epidemiology of syphilis infections among pregnant women in Tanzania: Analysis of the 2020 national representative sentinel surveillance - Bruno Sunguya; Erick Alexander Mboya; Mucho Mizinduko; Belinda Balandya; Amon Sabasaba; Davis Elias Amani; Doreen Kamori; George Ruhago; Rebecca Mkumbwa; Prosper Faustine; Werner Maokola; Veryeh Sambu; et al. (PLoS ONE, 2023)
Background Syphilis has detrimental effects on the health of the mother and that of both fetuses and newborns exposed in utero or at delivery. Understanding its local epidemiology is essential for policies, planning, and implementation of targeted preventive interventions. Using data from the 2020 National Sentinel Surveillance of pregnant women attending antenatal clinics (ANCs) in Tanzania we determined the prevalence and determinants of syphilis among pregnant women in Tanzania mainland. Methodology The ANC surveillance was conducted in 159 ANC sites from all 26 regions of Tanzania’s mainland from September to December 2020. It included all pregnant women 15 years and above on their first ANC visit in the current pregnancy during the survey period. Counseling for syphilis was done using standard guidelines at the ANC and testing was done using rapid SD Bioline HIV/Syphilis Duo test kits. Analysis was done using both descriptive statistics to determine the prevalence and characteristics of syphilis, whereas, logistic regressions were used to examine the independent association between syphilis and dependent variables. Results A total of 38,783 women [median age (Interquartile range (IQR)) = 25 (21–30) years] participated in the surveillance. Of them, 582 (1.4%) tested positive for syphilis. A wide regional variation was observed with the highest burden in Kagera (4.5%) to the lowest burden in Kigoma (0.3%). The odds of syphilis infections were higher among older women and those with no formal education. Compared with primigravids, women with 1–2, those with 3–4 and those with more than four previous pregnancies had 1.8 (aOR = 1.8, 95% CI: 1.2–2.5), 2.1 (aOR = 2.1, 95% CI: 1.4–3.1) and 2.6 (aOR = 2.6, 95% CI: 1.7–3.9) higher odds of syphilis infection respectively. Conclusion Syphilis is still prevalent among pregnant women in Tanzania with a wide regional disparity. Efforts to prevent new infections, screen pregnant women, and treat those infected should be strategized to include all regions and renewed emphasis on regions with high burden, and importantly among women who are multipara, with a low level of education, and advanced age.